DETERMINANTS OF THE QUALITY OF FINANCIAL STATEMENTS MSME - Farina, Khoirina; Opti, Sri (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThis study aims to examine and analyze the factors that affect the quality of MSME financial reports. The research is primary data obtained from questionnaires distributed and collected from respondents, namely MSME actors whose business activities are in the South Jakarta and East Jakarta Regions. The number of samples selected in this study were 231 respondents. This study uses quantitative methods and research data using partial least squares with SmartPLS software. The results of the study prove that the quality of MSME financial reports is significantly and positively influenced by the variables of educational background, business size and information technology. While other variables such as education, information and socialization have no effect. In relation to the implementation of MSME actors on the quality of financial reports by using SAK EMKM, so far MSME actors are still facing many obstacles such as not making financial reports according to standards, recording not routinely. This is because most MSME actors have low education so they do not understand the preparation of financial statements.Keywords: Quality of Financial Reports; MSMEs; SAK EMKM